Simultaneous tuning of the dielectric property and photo-induced conductivity in ferroelectric Ba0.7Ca0.3TiO3 via la doping - Jaiban,P. (Elsevier, 2015)
© 2015 Elsevier B.V. All rights reserved. (Ba0.7Ca0.3)1-1.5xLaxTiO3 ceramics with x=0-0.03 were prepared using a solid state sintering method. All ceramics exhibit ferroelectric state at maximum temperatures, Tm, between 340 and 383 K. Upon increasing La3+ content, although the maximum temperature of permittivity becomes lower (well correlated with the decrease of tetragonallity), the dielectric response is significantly higher near room temperature for the x=0.03 sample. Furthermore, the conductivity shows clear enhancement under ultra-violet (UV) irradiation. This enhancement becomes larger upon increasing La content, which correlates with the decrease in activation energy extracted from the temperature-dependent conductivity. The results here suggest that BCT properties may be largely tunable by La doping, which could be applied with much potential use with ferroelectric devices and in optoelectronics.